7-year efficacy and safety of iStent inject trabecular micro-bypass in combined and standalone usage - Hengerer, Fritz; Auffarth, Gerd U.; Conrad-Hengerer, Ina (Advances in therapy, 2024)
Introduction: This study evaluated 7-year effectiveness and safety of second-generation trabecular micro-bypass implantation (iStent inject) either in combination with cataract surgery or as a standalone procedure (Combined or Standalone subgroups, respectively) in eyes with open-angle glaucoma. Methods: This prospective, non-randomized, unmasked, longitudinal study included 125 consecutive iStent inject cases of a single surgeon at a large German academic hospital. Patients had considerable preoperative disease burden, with mean intraocular pressure (IOP) of 23.5 mmHg, 84.8% of eyes on >= 2 medications, and 38.4% of eyes with prior glaucoma surgery. IOP, medications, adverse events, and secondary surgeries were assessed through 7 years in the Overall cohort and in Combined (n = 81) and Standalone (n = 44) subgroups. Results: Over 7-year follow-up, mean IOP decreased by 36.2-40.0% in Overall eyes, 34.1-38.9% in Combined eyes, and 39.5-43.5% in Standalone eyes (p < 0.001 at all timepoints for all groups). Meanwhile, mean medications decreased by 59.3-71.3% in Overall eyes, 57.9-69.0% in Combined eyes, and 62.1-76.2% in Standalone eyes (p < 0.001 at all timepoints in all groups). At last follow-up (mean 77.4 months; 92.8% of patients with last visit at 6 or 7 years), 83.7% of Overall eyes, 82.3% of Combined eyes, and 86.4% of Standalone eyes had achieved >= 20% IOP reduction vs preoperative. At last follow-up vs preoperative, 100% of eyes in all groups had the same or lower IOP and 100% had the same or lower medication regimen. Safety outcomes were favorable, with no filtration surgeries and only 4.84% of eyes experiencing clinically significant visual field loss over 7 years of follow-up. Conclusion: iStent inject implantation with or without phacoemulsification produced significant and durable 7-year reductions in IOP (similar to 34-44% reduction) and medications (similar to 58-76% reduction) while preventing filtering surgery in this cohort of patients with relatively high preoperative disease burden. Combined and Standalone cases had similarly favorable effectiveness and safety.
Gesehen am 28.05.2024
Im Titel ist "inject" schräg gestellt